Evaluasi Penegakan Hukum Anti Monopoli Antara Kepentingan Pasar dengan Kepentingan Publik dalam UU No. 5 Tahun 1999 Tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Muta’ali, Abdul Yazid; Hendrawarman, Hendrawarman (Postulat, 2025)
This article discusses the evaluation of law enforcement in Law No. 5 of 1999 concerning The prohibition of monopolistic practices and unfair business competition, with a focus on the balance between market interests and public interests. Law enforcement in Indonesia is faced with various challenges, including limited resources, lack of accurate data, and political influence that hinder the effectiveness of the Business Competition Supervisory Commission (KPPU) in supervising monopolistic practices. This article analyzes the effectiveness of law enforcement based on the existing regulatory framework and highlights the dilemma faced between promoting market efficiency and consumer protection. The evaluation results show that law enforcement often prioritizes market interests, which can potentially harm the public interest. The obstacles faced, including legal uncertainty and the influence of large business actors, are also identified as obstacles in achieving the desired balance. Therefore, this article suggests the need to increase the capacity of the KPPU, educate the public, and adjust regulations to optimize fair and effective law enforcement. These findings are expected to provide recommendations for improving the supervision system for monopolistic practices in Indonesia.